p53-protein over-expression and gene mutational of oral carcinoma in-situ - Mei Syafriadi; Takashi Saku (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
We had been reported histological types of oral carcinoma in-situ (oral CIS), such as basaloid, verrucous, and acanthothic/ atrophic types. We considered that they have different histological appearance influenced by molecular behavior. To understand the molecular behavior of them we examined p53 exon 4–8 gene mutation and their protein expression. Using 35 cases formalin-fixed paraffin sections of oral CIS and 10 cases of mild and moderate squamous epithelial displasia (SED) as a control were subjected to p53 immunohistochemistry. In the next step all cases were subjected to p53 gene mutations analysis by laser capturing microdissection and direct sequencing of PCR product for exon 4–8. Showed that p53-protein over-expression were found in basal layer of SED and the p53 protein over-expression were confined in the whole layer of CIS-basaloid type, basal and parabasal layers of CIS-verrucous type, and sporadically in the basal layer of CIS-acanthothic type. Mutational analysis for p53 gene showed 43% of total cases of CIS had p53 gene mutation therefore CIS-basaloid type had mutations more frequently than the other types and mutation in exon 8 more dominant than other exons, which had some common mutation at codons 196, 248, 282, 291, and 306, while no particular mutations were found in control (SED).Our criteria to diagnose several types of oral carcinoma in-situ by p53 protein expression and mutational analysis could be used to understand molecular behavior of CIS.